IMPACT OF COMORBIDITIES ON THE CLINICAL OUTCOMES OF PATIENTS WITH PULMONARY HYPERTENSION - Razan Khalid Thabit,⁠ Dr.Abdullah Sulaiman Alqefari,⁠ Dr.Manal Abdulbaqi Alibrahim,⁠ Mohammed Ghalab Alanazi, Dr.Abdullah Aedh Alrasheed, Mohammed Qasem Masmali, ⁠Easa Wali Umar Magfory,⁠ Sultan Mohammed Hamdan Allihybi⁠⁠, Randa Abdulaziz Alkhalaf,⁠⁠; Anas Sulaiman Aloraini,⁠ Rayan Mohammed Almazroo, Hafez Mohammed Ali Darraj, ⁠Batul Ali Mohammed Mahdi, Alaa Hayas Abdullah Alzahrani, Khaled Abdullah Abuhayyah (Chelonian Research Foundation, 2022)
Comorbidities are common in chronic obstructive pulmonary disease (COPD) and have a major influence on patients' quality of life, frequency of exacerbations, and survival. There is a growing body of research indicating that certain illnesses are more prevalent among individuals with COPD compared to the general population. Furthermore, these additional health conditions have a major influence on the overall well-being and prognosis of COPD patients. While the specific processes are yet unknown, it is very probable that many comorbidities arise as a consequence of the persistent inflammatory condition that is characteristic of COPD. Key challenges in the clinical management of COPD are identifying newly emerging comorbidities, assessing the influence of comorbidities on patient symptoms, managing COPD and comorbidities simultaneously, and making precise prognoses. Most comorbidities in COPD should be handled in the normal manner, and the existence of comorbidities seldom affects the specific therapy of COPD. Regrettably, comorbidities often go unnoticed and get inadequate treatment. This analysis specifically examines the prevalence and distribution of 10 significant coexisting medical conditions in individuals diagnosed with chronic obstructive pulmonary disease (COPD). Additionally, we highlight the significant influence on the prognosis and the concerns for managing the condition. This review will emphasize the significance of identifying and managing comorbidity in the care of patients with COPD. Keywords: prevalence, death rates, chronic bronchitis, emphysema, chronic obstructive pulmonary disease (COPD).